Floral structure of Mesanthemum radicans (Eriocaulaceae, Poales): morphological and anatomical novelties - Silva, Arthur de Lima [UNESP]; Stützel, Thomas; Trovó, Marcelo; Coan, Alessandra Ike [UNESP] (Elsevier, 2021)
Mesanthemum is a genus of Eriocaulaceae endemic to Africa whose petals are free at the base and fused from the middle region up to the apex. Detailed studies on its floral morphology are scarce and based only on exsiccates, while the floral anatomy remains understudied. However, information regarding its floral structure is key to understanding the evolution of Eriocaulaceae. We provided details on the floral morphology and anatomy of M. radicans to evaluate characters with taxonomic and evolutionary importance. The flowers of M. radicans have tightly packed floral parts and reduced vasculature. They have petals with three vascular bundles, in contrast to a single bundle in petals of other Eriocaulaceae. Each petal receives three vascular traces, as in Xyridaceae, but they diverge from common petal-inner stamen traces. The type of petal fusion and the presence of stamens at two heights in M. radicans are probably related to space constraints in the floral buds of this species. However, further studies are necessary to comprehend the developmental processes that lead to petal fusion in Mesanthemum. The fact that the outer stamens are shorter than the inner ones can be interpreted as a step towards their loss in Paepalanthoideae. Furthermore, the petal glands and the carpellodes share characteristics, such as shape and the presence and location of papillae, that may be diagnostic for Eriocaulaceae.
Keywords: Carpellode; Petal fusion; Petal gland; Xyridaceae; Xyrids